The Influence Of Product Quality, Beauty Influence, And Product Design On Wardah Skincare User Satisfaction In Batam City - Deska Fitrianika; Inda Sukati (Primanomics : Jurnal Ekonomi & Bisnis, 2024)
The aim of this study was to explore how the quality of beauty products and product design impact the satisfaction levels of Wardah skincare users in Batam City. Employing a descriptive approach with quantitative methods, the study targeted a population of 100 respondents. The sample size was determined using the Slovin formula, resulting in 100 respondents selected through a simple random sampling technique. Data collected underwent analysis using a multiple linear regression model. To assess data quality, classical assumptions, influences, and research hypotheses, multiple linear regression testing and SPSS software were utilized. The outcomes of the multiple linear regression tests revealed that product quality contributed to 35.4% of user satisfaction, while the influence of beauty accounted for 46.3% and product design for 16.2% of user satisfaction. The coefficient of determination (R2) stood at 79.3%, indicating that 79.3% of Wardah skincare user satisfaction can be elucidated by factors such as Wardah product quality, beauty influence, and product design. The results from hypothesis testing demonstrated a positive and significant correlation between product quality, beauty influence, and product design, and Wardah skincare user satisfaction in Batam City.